Soil-vegetation relationships of a bitter-brush-sagebrush association in northwestern Colorado - Cunningham, Hugh, author; Terwilliger, Charles, Jr., advisor; Mogren, Edwin W., committee member; Berg, W. A., committee member (Colorado State University. Libraries, 1971)
Site evaluation is becoming increasingly important as management of forest and rangelands intensifies. Soil-vegetation studies may help to provide a basis for site prediction on disturbed areas, or areas considered for type conversion. In this study soil properties were compared with native vegetation responses in a bitterbrush (Purshia tridentata), sagebrush (Artemisia ~•) association on a single parent material. The effort was directed toward isolating those soil characteristics which are most valuable as indicators of potential vegetation production. Detailed soil and vegetation data were collected from 22 stands, all occurring on a sandy parent material, within the same climatic region, and on similar topography. Stands were selected along gradients of vegetation growth responses, i.e., changes in species composition, shrub height, shrub density, vigor, etc. Soil profiles at each location were described, and samples were collected for laboratory analysis of physical and chemical characteristics. Analysis of data by simple correlation and stepwise multiple regression revealed that the amount of gravel and rock occurring as a layer in the soil profile is the most important factor for predicting bitterbrush production on the area studied. The negative effect of the coarse fragments layer on production of the deep-rooted shrub is thought to indicate less moisture penetration. Other negative factors found important to the prediction equation were: available P, available K, and percent sand, all in the top six inches. The only positive factor appearing in the prediction equation was available P at a depth of 6-12 inches. Silver sagebrush production was apparently influenced by more favorable moisture conditions near the surface than by restriction of deep penetration of water. Thickness of the A horizon, percent organic matter in the 6-12 inch zone, and extractable Mg in the 12 ... 24 inch strata were positive factors, while depth of abundant rooting and extractable Mg in the surface six inches were negative factors included in the prediction equation. Measurements must be taken of chemical and physical properties at several depths in order to predict total forage production. Surface soil measurements found important were: available K and percent sand in the top six inches. Their effects were negative. The amount of gravel and rock, and the thickness of the B2 horizon were also negatively correlated with production, while available K and percent coarse sand in the 12-24 inch layer had a positive influence on production.
Keywords: Soils; Ecology; Purshia tridentata; Sagebrush